PENENTU AWAL WIRAUSAHA SALAH SATUNYA ADALAH ANALISA PASAR DI GORONTALO - Saleh Modjo, Ardiyanto (Kilau Publishing, 2023)
Market analysis is one of the weapons as well as a shield for entrepreneurs, so that their businesses have resilience against competition. Market analysis will be the